(untitled) (Nigerian Journal of Physiological Sciences, 2023)
Monosodium glutamate (MSG) has been known to cause neurodegeneration, due to its ability to trigger excitotoxicity, and the hippocampus is one of the most affected regions. Therefore, Phoenix dactylifera (P. dactylifera) and polyphenols was employed in this study to mitigate on the deleterious effect of monosodium glutamate on the dentate gyrus of Wistar rats. Forty-eight male Wistar rats weighing between 120-150g was used for the study. The Wistar rats were grouped into eight, (n=6). Groups 1-8 received 1.6mL/kg normal saline, 4000mgmonosodium glutamate for 7-days, 4000mgmonosodium glutamate for 7-days and 100mgcaffeic-acid for 14-days concurrently, 4000mgmonosodium glutamate for 7-days and 100mgPhoenix dactylifera for 14-days concurrently, 4000mgmonosodium glutamate for 7-days and 100mgluteolin for 14-days concurrently, 100mg. caffeic-acid for 14-days followed by 4000mgmonosodium glutamate for 7-days, 100mgPhoenix dactylifera for 14-days followed by 4000mgmonosodium glutamate for 7-days and 100mgluteolin for 14-days followed by 4000mgmonosodium glutamate for 7-days respectively. After the treatments, the rats underwent behavioural tests, and subsequently, the brain tissues were processed for histological and biochemical analyses. The activities of P. dactylifera and polyphenols ameliorated the deleterious effect of monosodium glutamate, through increased spontaneous alternation of the experimental animals, dominant matured granule cells of the dentate gyrus and modulated the activities of superoxide dismutase, glutathione peroxidase and malondialdehyde in the of male Wistar rats. Therefore, this study revealed that P. dactylifera and polyphenols ameliorated monosodium glutamate toxicity in the dentate gyrus of Wistar rats.